Intelligent decision technologies 2017. Proceedings of the 9th KES International Conference on Intelligent Decision Technologies (KES-IDT 2017) /: Proceedings of the 9th KES International Conference on Intelligent Decision Technologies (KES-IDT 2017). Part II : (2018) - Unknown
No abstract available